Compassion Satisfaction, Burnout and Compassion Fatigue within the Context of the Dimensions of the Professional Quality of Life Scale in Nurses: A Cross-Sectional Study - Çelebi, Evrim; Can, Hafize Ozturk (My University, 2022)
Objective: This study was conducted to determine the\rprevalence of compassion satisfaction, burnout and compassion fatigue,\rwhich are the dimensions of the professional quality of life, among\rnurses working in a university hospital, and the affecting demographic\rand occupational factors. Material and Methods: The population of\rthis cross-sectional study included 349 nurses and the study was completed\rwith 253 nurses (72.5%). The data were collected using the personal\rinformation form and “Professional Quality of Life Scale”\rdeveloped by Stamm. Results: The mean scores obtained by the nurses\rparticipating in the study were as follows: 32.08±9.09 for the compassion\rsatisfaction subscale, 25.75±5.87 for the burnout subscale, and\r18.50±7.57 for the compassion fatigue subscale. The level of compassion\rsatisfaction was significantly higher among nurses working in surgical\rclinics. The burnout levels of the participants were affected by\rthe marital status. The married nurses obtained significantly higher\rmean scores from the burnout subscale. There were not differences between\rthe participants’ compassion fatigue levels in terms of the demographic\rvariables. Conclusion: While the participating nurses had\rlow levels of compassion satisfaction, they had moderate levels of\rburnout, and high levels of compassion fatigue.
Keywords: Sosyal Çalışma; İşletme; Sağlık Bilimleri ve Hizmetleri; Hemşirelik; Psikoloji